Representasi Kearifan Lokal Melalui Tagline Destination Branding Kediri Berbudaya oleh Pemerintah Kabupaten Kediri - Berliana Widiyaningtyas; Azizah, Siti (Jurnal PUBLIQUE, 2025)
This study aims to understand how the Kediri Regency Government represents local wisdom through the tagline ‘Kediri Berbudaya’ as a destination branding strategy. The approach used is descriptive qualitative with data collection techniques through participatory observation, in-depth interviews, and documentation. The research findings indicate that the tagline “Kediri Berbudaya” serves not only as a regional promotional slogan but has also become a collective symbol that internalises local cultural values into the daily lives of the community. This representation of local wisdom is manifested through visualisation in public spaces, the introduction of traditional regional attire such as Wastra Kediri, Wdihan Kadiri, and Ken Kadiri, and support for interfaith religious activities as concrete expressions of tolerance and social cohesion. The tagline plays a strategic role in strengthening regional identity and fostering a participatory and sustainable cultural narrative amid the tide of modernisation.